Clinical Pharmacology of Frequently Used Intravenous Drugs During Bariatric Surgery in Adolescents - D. Vaughns, Janelle; C. Ziesenitz, Victoria; N. van den Anker, John (Current Pharmaceutical Design, 2015)
Obesity represents one of the most important public health issues according to the World Health Organization. Additionally, in a recent National Health and Nutrition Survey of 2011-2012, approximately 17 % of children and adolescents in the United States were considered obese. The obesity rate is higher within the adolescent age group as compared to preschool children. Childhood obesity is particularly problematic, because the co-morbid disease states which accompany obesity may require frequent pharmacotherapy and/ or surgical intervention. Despite the potential for increased pharmacotherapy among obese patients, there is a paucity of dosing guidelines for this special population. Optimal drug dosing in obese pediatric patients has not been sufficiently explored as the present data available are mostly specific for obese adults. In this review, we present an overview concerning what is currently known about the pharmacokinetics and pharmacogenetics of frequently used drugs including midazolam, fentanyl and its newer derivatives, morphine, ketamine, acetaminophen, dexmedetomidine and enoxaparin in obese adolescents undergoing bariatric surgery. We will also summarize the current dosing recommendations of anesthetic drugs in bariatric anesthesia.
Keywords: opioids